Brody : a Galician border city in the long nineteenth century - Kuzmany, Börries (Studia Judaeoslavica, 2017)
"An urban biography, Brody : A Galician Border City in the Long Nineteenth Century reconciles 150 years of the town's socioeconomic history with its cultural memory. The first comprehensive study of this city under Habsburg-Austrian rule, Börries Kuzmany advises against reading urban history solely through the national lens. Besides exploring Brody's extraordinary ethno-confessional structure--Jews, Poles, and Ukrainians--Kuzmany examines the interrelation between the city's geographical location at the imperial border, its standing as a key commercial hub in East-Central Europe, and its position as a major springboard for the dissemination of the Haskalah in Galicia and the Russian Empire. After delving into the contradictory perceptions of Brody in travelogues, fiction and memory books, Kuzmany uses contemporary and historical photographs to provide an illustrated walking tour of this now Ukrainian town"--Publisher description.